2007
DOI: 10.1111/j.1750-3639.2007.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Octarepeat Region in Neuroprotective Function of the Cellular Prion Protein

Abstract: Structural alterations of the cellular prion protein (PrP C ) seem to be the core of the pathogenesis of prion diseases. However, the physiological function of PrP C remains an enigma. Cell culture experiments have indicated that PrP C and in particular its Nterminal octarepeat region together with the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathways have a fundamental involvement in neuroprotection and oxidative stress reactions. We used wild-type mice, PrP knockout (Prnp -/-) animals and transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
100
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 42 publications
8
100
2
2
Order By: Relevance
“…These findings suggest that PrP C participates in the modulation of the activity of these enzymes and/or PrP C itself functions as an antioxidant molecule. Moreover, it has been reported that the flexible N-terminal domain of PrP C , which we have shown contains heminbinding sites, is influential in cellular responses to oxidative stress (50,51). This suggests that the peroxidase activity of hemin-PrP C complexes may play a protective role against oxidative stress.…”
Section: Discussionsupporting
confidence: 50%
“…These findings suggest that PrP C participates in the modulation of the activity of these enzymes and/or PrP C itself functions as an antioxidant molecule. Moreover, it has been reported that the flexible N-terminal domain of PrP C , which we have shown contains heminbinding sites, is influential in cellular responses to oxidative stress (50,51). This suggests that the peroxidase activity of hemin-PrP C complexes may play a protective role against oxidative stress.…”
Section: Discussionsupporting
confidence: 50%
“…38 A neuroprotective activity of PrP C was also reported by Mitteregger et al who revealed that both the C-terminal GPI anchor and the unstructured N-terminal domain are required for this physiological activity. 39 Thus, PrP C might act as a signaling molecule at the cell surface to promote stress-protective signaling under physiological conditions, which can be switched to toxic signaling through an interaction with β-sheet-rich conformers. Similarly to other GPI-anchored proteins involved in signal transduction, PrP C may act as a co-receptor in concert with a transmembrane protein to transduce the signal into the cell.…”
Section: Perspectivesmentioning
confidence: 99%
“…The design of the Sho mutants was based on PrP mutants that have been characterized previously. PrP⌬N, a mutant lacking large parts of the intrinsically disordered N terminus (⌬aa 27-89), can promote propagation of infectious prions (14) but shows an impaired neuroprotective activity (9,15). PrP⌬HD lacks the highly conserved internal hydrophobic domain (⌬aa 113-133) and is characterized by a neurotoxic potential that can be blocked by the co-expression of wild type (WT) PrP C (9,(17)(18)(19).…”
Section: Sho Mutants Devoid Of the N-terminal Domain Or The Internal mentioning
confidence: 99%
“…13). Interestingly, the octarepeat region in the N-terminal domain as well as the C-terminal GPI anchor are dispensable for the generation of infectious prions (8,14) but are required for the stress-protective activity of PrP C (9,15). Although in the majority of prion diseases there is a correlation between the accumulation of PrP Sc , formation of infectious prions, and neurodegeneration, there are some interesting exceptions.…”
mentioning
confidence: 99%